Evaluation of the Distance Learning Learning Model of the Priority Program of the Ministry of Religious Affairs of the Republic of Indonesia - Moh. Ali; Fani Juliyanto Perdana; Alwy Husein Prawironegoro; F. Alamul Huda; Ari Kartiko (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to evaluate the distance learning model implemented under the Priority Program of the Ministry of Religious Affairs of the Republic of Indonesia at Universitas Islam Negeri (UIN) Siber Syekh Nurjati Cirebon. The research employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and analysis of online learning documents. The findings indicate that the distance learning model at UIN Siber Syekh Nurjati Cirebon integrates multiple approaches, including synchronous, asynchronous, blended learning, and collaborative models supported by a Learning Management System (LMS). This model has proven effective in enhancing accessibility and flexibility in Islamic religious education, as well as encouraging a paradigm shift toward student-centered learning. Nevertheless, the study also identifies several challenges, such as limited access to technology, inadequate internet connectivity, reduced social interaction, and issues related to students’ mental and emotional readiness. The study concludes that while the distance learning model is relatively effective in achieving the objectives of religious education, it requires stronger institutional policies, increased faculty capacity building, and sustained pedagogical innovation.